PENGARUH SISTEM PENGENDALIAN INTERNAL, AUDIT INTERNAL DAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD PADA LEMBAGA KEUANGAN NON-BANK - Satiman, Satiman; Suparmin, Suparmin (LPPM University 17 Agustus 1945 Samarinda, 2023)
The purpose of this study is to determine the influence of the internal control system, internal audit and good corporate governance on fraud prevention in non-bank financial institutions in the (pawning) sector using a sample of hj nawi branches in South Jakarta and around in 2022. The method used is a quantitative method. The data collection technique used is to distribute questionnaires to pawnshops. Population This study was 63 and the sample used was a saturated sample where the entire population was sampled. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis test. The data in this study were tested using the Software Statistical Package for Social Sciences (SPSS) version 25 The results of this study showed that the internal control system had no effect on fraud prevention, in accordance with the results of calculating the t-test, it was known that the value of 1.868 < 2,000 (calculated < t-table) and a significant value of 0.007 < 0.05. Thus, H0 is accepted and H1 is rejected, this shows that there is no partial influence between Internal Control on Fraud Prevention, while internal audits and good corporate governance affect fraud prevention.